2024
DOI: 10.1038/s41467-024-45336-6
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes augments group B Streptococcus infection by disrupting maternal immunity and the vaginal microbiota

Vicki Mercado-Evans,
Marlyd E. Mejia,
Jacob J. Zulk
et al.

Abstract: Group B Streptococcus (GBS) is a pervasive perinatal pathogen, yet factors driving GBS dissemination in utero are poorly defined. Gestational diabetes mellitus (GDM), a complication marked by dysregulated immunity and maternal microbial dysbiosis, increases risk for GBS perinatal disease. Using a murine GDM model of GBS colonization and perinatal transmission, we find that GDM mice display greater GBS in utero dissemination and subsequently worse neonatal outcomes. Dual-RNA sequencing reveals differential GBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Recently, a study indicated that intrauterine infection by Porphyromonas gingivalis was associated with increased uterine NK cell populations and decreased secretion of IL-18 in rat, accompanied by a reduction of TNF-α + T cells ( 106 ). Another study showed that the depletion of NK cells, mainly uterine NK cells, played a protective role in Group B Streptococcus (GBS) fetal invasion in GDM mice ( 107 ). Crespo et al.…”
Section: Maternal Gut Microbiota and The Immune Response During Pregn...mentioning
confidence: 99%
“…Recently, a study indicated that intrauterine infection by Porphyromonas gingivalis was associated with increased uterine NK cell populations and decreased secretion of IL-18 in rat, accompanied by a reduction of TNF-α + T cells ( 106 ). Another study showed that the depletion of NK cells, mainly uterine NK cells, played a protective role in Group B Streptococcus (GBS) fetal invasion in GDM mice ( 107 ). Crespo et al.…”
Section: Maternal Gut Microbiota and The Immune Response During Pregn...mentioning
confidence: 99%